2020
DOI: 10.21608/ejfsat.2020.14782.1085
|View full text |Cite
|
Sign up to set email alerts
|

The Sub Chronic Toxic Effect of Voodoo Extract on the Central Nervous System in Adult Male Albino Rats

Abstract: Introduction:Voodoo is a mixture of herbs and spices that are sprayed with a synthetic compound that mimics the effects of Cannabis. The widespread over-the-counter availability of these products made these compounds the 2 nd most common frequently used recreational drug after marijuana in teenagers and young adults. This study aimed to investigate the sub chronic toxic effects of Voodoo (Voodoo abuse) on the central nervous system (CNS) in adult male albino rats.Methodology: thirty adult male albino rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Methomyl is one of the most commonly used insecticides which was classified as an endocrine disrupter through World Wildlife Fund International in 1997 (Shun‐long et al, 2013). Exposure to methomyl during pregnancy has been reported to result in many histopathological alternations in liver, adrenal gland, and renal tissues (Mansour et al, 2008; Rachid et al, 2016). In their study, Rachid and Yousef (2013) reported that pregnant rats injected with methomyl showed many pathological changes in the adrenal glands and ovary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methomyl is one of the most commonly used insecticides which was classified as an endocrine disrupter through World Wildlife Fund International in 1997 (Shun‐long et al, 2013). Exposure to methomyl during pregnancy has been reported to result in many histopathological alternations in liver, adrenal gland, and renal tissues (Mansour et al, 2008; Rachid et al, 2016). In their study, Rachid and Yousef (2013) reported that pregnant rats injected with methomyl showed many pathological changes in the adrenal glands and ovary.…”
Section: Introductionmentioning
confidence: 99%
“…pregnancy has been reported to result in many histopathological alternations in liver, adrenal gland, and renal tissues (Mansour et al, 2008;Rachid et al, 2016). In their study, Rachid and Yousef (2013) reported that pregnant rats injected with methomyl showed many pathological changes in the adrenal glands and ovary.…”
mentioning
confidence: 99%